Modified polyaryletherketone composition, high performance liquid chromatography rotor sealing fin and preparation method of rotor sealing fin
By modified polyford etherone compositions, including ultra -high molecular measuring polyethylene, sheet structure fillers, and inorganic nano -nano -fillers, the problem of increased friction coefficient and increased wear of sealing materials under high temperature conditions, and realized the low friction coefficient The effect of low milling consumption is suitable for sealing parts of high temperature environments.
Patent Information
- Application Number
- CN202411440313.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-28
AI Technical Summary
The existing sealing materials have increased friction coefficient and wear volume under high temperature conditions, and cannot be used for a long time.
The modified polyethyl ether composition, including ultra -high molecular measuring polyethylene, sheet structure fillers (graphite or tungsten sulfide), and inorganic nano -fillers (silicon dioxide, magnesium oxide, etc.), the combination and amount of these materials Optimize and improve the friction performance and thermal conductivity of composite materials.
The effect of maintaining low friction coefficients and low milling consumption under high temperature conditions, especially under 260 ° C without oil conditions, the friction resistance of sealing parts can be maintained for a long time.
Smart Images

Figure BDA0005086172520000031 
Figure BDA0005086172520000041 
Figure BDA0005086172520000042
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sealing materials, and in particular relates to a modified polyaryletherketone composition, a high performance liquid chromatography rotor sealing sheet and a method for preparing the rotor sealing sheet. Background Art
[0002] In the related art, the traditional sliding sealing composition used for sealing components is usually a composite material made of high molecular polymer raw materials such as polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyether ketone (PEEK), etc., mixed with carbon fiber (CF), glass fiber (GF) as reinforcing fillers, and graphite (GR), molybdenum disulfide (MoS2) and the like as friction modifiers. However, although graphite has a good content effect, its lubrication effect is significantly affected by its degree of dispersion and dispersion stability, and the amount of addition needs to be precisely controlled; molybdenum disulfide exhibits excellent friction reduction effects at room temperature / low temperature, but its lubrication effect will be significantly reduced under high temperature environment. Therefore, seals made of the above composite materials may have problems of increased friction coefficient and increased wear under high temperature and harsh working conditions, especially under high temperature conditions above 260°C, and cannot be used for a long time.
[0003] Therefore, in view of the above technical problems, it is necessary to provide a composite material with low friction coefficient and low wear that can meet the application requirements under high temperature conditions. Summary of the invention
[0004] The purpose of the present invention is to provide a modified polyaryletherketone composition, a high performance liquid chromatography rotor sealing sheet and a method for preparing the rotor sealing sheet.
[0005] In a first aspect, the present invention provides a modified polyaryletherketone composition, which adopts the following technical solution:
[0006] A modified polyaryletherketone composition comprises the following raw materials by weight:
[0007] 45-75 parts of polymer material
[0008] Fiber filler 5-15 parts
[0009] Polytetrafluoroethylene 0-5 parts
[0010] Ultra high molecular weight polyethylene 15-20 points
[0011] 5-10 parts of lamellar structure filler
[0012] 1-5 parts of inorganic nanofiller;
[0013] Wherein, the polymer material is polyaryletherketone, or a mixture of polyaryletherketone and polyimide;
[0014] The molecular weight of the ultra-high molecular weight polyethylene is in the range of 1 million to 7 million;
[0015] The sheet structure material is graphite, tungsten disulfide or a mixture of the two.
[0016] By adopting the above scheme, ultra-high molecular weight polyethylene can significantly improve the friction performance of the composite material under high temperature, and the incorporation of lamellar structure fillers and inorganic nanofillers can improve the thermal conductivity and dispersion stability of each component in the composite material, thereby synergistically enabling the ultra-high molecular weight polyethylene to fully exert the improvement effect on the friction performance of the composite material, achieving the effect of maintaining a low friction coefficient and low wear for a long time under high temperature conditions, and being able to maintain friction resistance for a long time under high temperature conditions, especially under oil-free conditions at 260°C.
[0017] Furthermore, the polyaryletherketone is a mixture of one or more of polyetheretherketone, polyetherketone, polyetherketoneketone, polyetheretherketoneketone and polyetherketoneetherketoneketone. Polyaryletherketone (PAEK) is a type of raw material suitable for making high temperature resistant sealing products, mainly including polyetheretherketone (PEEK), polyetherketone (PEK), polyetherketoneketone (PEKK), polyetheretherketoneketone (PEEKK) and polyetherketoneetherketoneketone (PEKEKK). Specifically, products of domestic and foreign manufacturers such as BASF of Germany, Victrex of the United Kingdom, Panjin Zhongrun, Jilin Zhongyan, Haoran Special Plastics, Kingfa Technology, Changchun Jida Special Plastics, etc. can be selected.
[0018] Furthermore, the molecular weight of the ultra-high molecular weight polyethylene is in the range of 1 million to 5 million. The higher the molecular weight of the ultra-high molecular weight polyethylene, the worse its affinity with other raw materials and its dispersion stability in the composite material system. Too high a molecular weight is not conducive to processing, so the ultra-high molecular weight polyethylene in the above molecular weight range is better.
[0019] Furthermore, the lamellar structure material is made of graphite and tungsten disulfide mixed in a weight ratio of 1: (0.1-1.5). Both graphite and tungsten disulfide have high thermal conductivity and self-lubricating properties. The use of the two in the above ratio is conducive to reducing the friction coefficient of the composite material, and can also significantly improve the thermal conductivity of the composite material. Under high temperature conditions, heat can be quickly conducted and diffused, reducing the negative impact of uneven heat distribution or concentrated layout on the performance of ultra-high molecular weight polyethylene.
[0020] Furthermore, the amount of the lamellar structure material is 20-50wt% of the amount of the ultra-high molecular weight polyethylene, and the amount of the inorganic nanofiller is 5-30wt% of the amount of the ultra-high molecular weight polyethylene. Controlling the amount of the filler within the above range is conducive to improving the friction performance of the composite material under high temperature conditions, while not causing processing difficulties or deterioration of the mechanical properties of the composite material due to excessively high amounts.
[0021] Furthermore, the inorganic nanofiller is a mixture of one or more of silicon dioxide, magnesium oxide, and aluminum oxide. The three inorganic fillers are easy to obtain, have good high-temperature stability, and have a better effect of synergistically improving the friction performance of composite materials, and to a certain extent also increase the dimensional stability and crack resistance of composite products under high temperature conditions; the inorganic nanofiller is preferably a filler with high sphericity and high thermal conductivity, which can better improve the friction performance of composite materials at high temperatures; the inorganic nanofiller is further preferably magnesium oxide.
[0022] Furthermore, the fiber filler is one or more of carbon fiber, aramid fiber and glass fiber.
[0023] In a second aspect, the present invention provides a high performance liquid chromatography rotor seal, which is made of the modified polyaryletherketone composition. The high performance liquid chromatography rotor seal of the present invention has low friction coefficient and low wear characteristics, and its friction resistance can be maintained for a long time under high temperature conditions, especially under oil-free conditions at 260°C.
[0024] In a third aspect, the present invention provides a method for preparing a rotor sealing sheet, the specific steps of which are: weighing raw materials according to a ratio, mixing them evenly, and then using a granulating device to granulate the evenly mixed raw materials to form injection molding particles, and then sending the injection molding particles into an injection molding device for injection molding to obtain a rotor sealing sheet. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the present application will be further described in detail with reference to the examples below. Unless otherwise specified, various raw materials can be obtained from commercial sources, and the following examples / comparative examples only select raw materials of some brands / grades / specifications for illustrative purposes, which are not intended to limit the present invention. When implementing the present invention, specific raw material types and specifications can be selected as needed.
[0026] The specific sources and specifications of raw materials of various embodiments / comparative examples of the present invention are shown in Table 1.
[0027] Table 1. Raw material source specifications
[0028]
[0029]
[0030] Examples 1-6
[0031] Examples 1-6 all relate to a modified polyaryletherketone composition. Specifically, the raw materials are weighed according to the proportions in Table 2, dry-mixed and then put into a two-axis melt extruder, extruded and granulated at 350-400° C. to obtain a granular modified polyaryletherketone composition that can be used for injection molding. The obtained modified polyaryletherketone composition can be used for injection molding of rotor seals for high performance liquid chromatography.
[0032] Table 2. Raw material ratios of Examples 1-6
[0033] raw material Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Polyetheretherketone / kg 15 10 20 20 20 25 Polyetherketone / kg 30 30 20 20 25 25 Polyetherketoneketone / kg / 10 20 20 25 20 Polyimide / kg / / / 1 2.5 5 Carbon fiber / kg 5 3 5 / 8 5 Aramid fiber / kg / 2 / 5 5 5 Glass fiber / kg / 2 4 6 / 5 Polytetrafluoroethylene / kg / 1 2 3 4 5 Ultra high molecular weight polyethylene / kg 15 16 17 18 19 20 Graphite / kg 5 6 7 8 9 10 Nano silicon dioxide / kg 1 2 3 4 5 5
[0034] Comparative Examples 1-6
[0035] Comparative Examples 1-6 all relate to a modified polyaryletherketone composition, and are all based on Example 6. The difference from Example 6 is that the raw material ratios are different, as shown in Table 3 for details.
[0036] Table 3. Raw material ratios of Example 6 and Comparative Examples 1-6
[0037]
[0038]
[0039] Dynamic friction coefficient test:
[0040] The friction coefficient was tested using the experimental device and method of HG / T2729-2012 Method A: the modified polyaryletherketone compositions prepared in Examples 1-6 were respectively heated to melt at 350-400°C and 1100-1300 kgf / cm 2 Conditions: extruded to a mold at 200℃, cooled and formed, cut to obtain a 63mm*63mm*2mm sample with a flat surface and smooth edges; test conditions: the sheet is 250mm long and 130mm wide, the sample sliding distance is 130mm, the test speed is 150±3mm / min, the total mass of the slider, sample and double-sided adhesive tape is 200±5g, the test temperature is 25℃, and the humidity is 40%. Repeat 3 groups of experiments, and record the arithmetic mean of the dynamic friction coefficient as the final experimental result, as shown in Table 4 below:
[0041] Wear test:
[0042] The modified polyaryletherketone compositions prepared in Examples 1-6 were respectively used to make rotor seals (3 mm in thickness, 1300 mm in diameter), the initial weight of the rotor seals was measured, and a wear test was conducted at room temperature / 260°C and in an oil-free state, with a continuous operation at a speed of 10,000 rpm. The wear amount of the seals was measured at 12h / 48h after the start of the experiment, and the wear rate was calculated (wear rate = wear amount / initial weight*100%). Three groups of experiments were repeated, and the arithmetic mean of the wear rate was taken as the final experimental result, as shown in Table 4 below.
[0043] Table 4. Test results of Examples 1-6 and Comparative Examples 1-6
[0044]
[0045] From the experimental data in Table 4, we can see that:
[0046] The dynamic friction coefficient of the modified polyaryletherketone composition obtained by the implementation of the present invention is as low as 0.152-0.192, and the wear rate of the wear test under high temperature conditions (260°C) is as low as 0.42%-0.45% for 12h, and as low as 0.82%-0.95% for 48h. This shows that the modified polyaryletherketone composition obtained by the present invention has the characteristics of low friction coefficient and low wear under high temperature conditions, can be used for a long time under high temperature conditions, and is suitable for making seals for use in high temperature environments, such as rotor seals for high performance liquid chromatography.
[0047] At the same time, compared with Example 6, the friction coefficient of the composition obtained by Comparative Examples 1-6 increases, the wear rate is higher under high temperature conditions, and as the wear time increases, the wear rate of the comparative example decreases more significantly. Only adding ultra-high molecular weight polyethylene, lamellar structure filler (graphite) and inorganic nanofiller (nano-silicon dioxide), or only adding molybdenum dioxide commonly used in related technologies, can not effectively inhibit the increase in wear as the wear time increases. Under the same temperature and time conditions, the wear rate of the test piece obtained by the composition of the present invention at high temperature increases less. It shows that ultra-high molecular weight polyethylene, lamellar structure filler and inorganic nanofiller have the effect of synergistically reducing the friction coefficient of the composite material and inhibiting the increase in wear rate at high temperature.
[0048] Examples 7-10
[0049] Examples 7-10 are all based on Example 6, and the difference from Example 6 is that a mixture of equal amounts of graphite and tungsten disulfide is used as a lamellar structure filler instead of graphite; the proportions of the graphite and tungsten disulfide mixtures used in Examples 7-10 are different, as shown in Table 5 for details.
[0050] Table 5. Graphite and tungsten disulfide ratios for Examples 7-10
[0051] Examples Example 7 Example 8 Example 9 Example 10 Graphite / Tungsten disulfide (weight ratio) 1:0.1 1:0.5 1:1 1:1.5
[0052] Samples were prepared using the compositions obtained in Examples 7-10, respectively, and the dynamic friction coefficient and wear rate were tested. The test results are recorded in Table 6.
[0053] Table 6. Test results of Examples 6-9
[0054]
[0055] It can be seen from the experimental data in Table 6 that compared with adding graphite alone in Example 6, after adding the mixture of graphite and tungsten disulfide in Examples 7-10, the dynamic friction coefficient of the composition is slightly reduced and the wear rate is slightly reduced, and the effect is better. At the same time, it can be seen from the test data that when the weight ratio of graphite to tungsten disulfide is 1:1, the effect of reducing the friction coefficient and inhibiting the increase in the wear rate is better.
[0056] Examples 11-13
[0057] Examples 11-13 are all based on Example 9, and the difference from Example 9 is that: under the premise that the total amount of inorganic nanofillers added remains unchanged, different types of inorganic nanofillers or mixed inorganic nanofillers are selected, as shown in Table 7 for details.
[0058] Table 7. Composition of inorganic nanofillers in Examples 11-13
[0059]
[0060] Samples were prepared using the compositions obtained in Examples 11-13, respectively, and the dynamic friction coefficient and wear rate were tested. The test results are recorded in Table 8.
[0061] Table 8. Test results of Examples 9 / 11-13
[0062]
[0063] It can be seen from the experimental data in Table 8 that the addition of one or a mixture of nano-silicon dioxide, nano-magnesium oxide, nano-aluminum oxide has little effect on the dynamic friction coefficient of the composition, and the test results only change slightly; at the same time, it is worth noting that with the extension of working time, the wear rate of Example 12 using nano-magnesium oxide as the inorganic nano-filler has the smallest increase, and the wear rate increases by 0.2% when the test time is extended from 12h to 48h. This shows that the synergistic effect is best when nano-magnesium oxide is used as an inorganic nano-filler and mixed with ultra-high molecular weight polyethylene and lamellar structure fillers.
[0064] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A modified polyaryletherketone composition, characterized in that: Including the following raw materials by weight: Wherein, the polymer material is polyaryletherketone, or a mixture of polyaryletherketone and polyimide; The molecular weight of the ultra-high molecular weight polyethylene is in the range of 1 million to 7 million; The sheet structure material is graphite, tungsten disulfide or a mixture of the two.
2. The modified polyaryletherketone composition according to claim 1, characterized in that The molecular weight of the ultra-high molecular weight polyethylene is in the range of 1 million to 5 million.
3. The modified polyaryletherketone composition according to claim 1, characterized in that The sheet structure material is formed by mixing graphite and tungsten disulfide in a weight ratio of 1: (0.1-1.5).
4. The modified polyaryletherketone composition according to claim 3, characterized in that The content of the sheet structure material accounts for 20-50wt% of the content of the ultra-high molecular weight polyethylene, and the content of the inorganic nano filler accounts for 5-30wt% of the content of the ultra-high molecular weight polyethylene.
5. The modified polyaryletherketone composition according to claim 1, characterized in that: The inorganic nano filler is a mixture of one or more of silicon dioxide, magnesium oxide and aluminum oxide.
6. The modified polyaryletherketone composition according to claim 5, characterized in that The inorganic nano filler is magnesium oxide.
7. The modified polyaryletherketone composition according to any one of claims 1 to 6, characterized in that: The fiber filler is one or more of carbon fiber, aramid fiber and glass fiber.
8. The modified polyaryletherketone composition according to any one of claims 1 to 6, characterized in that: The polyaryletherketone is a mixture of one or more of polyetheretherketone, polyetherketone, polyetherketoneketone, polyetheretherketoneketone and polyetherketoneetherketoneketone.
9. A high performance liquid chromatography rotor seal, characterized in that: The modified polyaryletherketone composition is prepared from the modified polyaryletherketone composition according to any one of claims 1 to 8.
10. A method for preparing a rotor sealing sheet, characterized in that: The specific steps are as follows: weigh the raw materials according to the ratio of any one of claims 1 to 8, mix them evenly, and then use a granulating device to granulate the evenly mixed raw materials to form injection molding particles, and then send the injection molding particles into an injection molding device for injection molding to obtain a rotor sealing sheet.
Citation Information
Cited By
Wear-resistant PEEK composite material and application of wear-resistant PEEK composite material in reversing valve for air bag pump
CN120737583A
Wear-resistant peek composite material and its application in reversing valve for wind bag pump
CN120737583B